Interfering with CSE1L/CAS inhibits tumour growth via C3 in triple‐negative breast cancer. Issue 5 (10th April 2022) - Ye, Mei; Chen, Yufei; Liu, Jianni; Tian, Jiawei; Wang, Xunda; Fok, Kin Lam; Shi, Jianwu; Chen, Hao
Abstract: Triple‐negative breast cancer (TNBC) is the most aggressive subtype of breast cancer. However, the treatment regimens for TNBC are limited. Chromosome segregation 1‐like (CSE1L), also called cellular apoptosis susceptibility protein (CAS), is highly expressed in breast cancer and plays a crucial role in the progression of various tumours. However, the involvement of CAS in TNBC remains elusive. In this study, we showed that the expression of CAS was higher in TNBC samples than in non‐TNBC samples in the Gene Expression Omnibus database. Knockdown of CAS inhibited MDA‐MB‐231 cell growth, migration and invasion. Further RNA‐seq analysis revealed that complement pathway activity was significantly elevated. Of note, complement component 3 (C3), the key molecule in the complement pathway, was significantly upregulated, and the expression of C3 was negatively correlated with that of CAS in breast cancer. Lower C3 expression was related to poor prognosis. Interestingly, the expression level of C3 was positively correlated with the infiltration of multiple immune cells. Taken together, our findings suggest that CAS participates in the development of TNBC through C3‐mediated immune cell suppression and might constitute a potential therapeutic target for TNBC.